The end : natural disasters, manmade catastrophes and the future of human survival - De Villiers, Marq (Thomas Dunne Books, 2008)
What is the fate of the world as we know it? Tsunamis, earthquakes, volcanoes, hurricanes, pandemics, cosmic radiation, gamma bursts from space, colliding comets, and asteroids—these things used to worry us from time to time, but now they have become the background noise of our culture. Are natural calamities indeed more probable, and more frequent, than they were? Are things getting worse? Are the boundaries between natural and human-caused calamities blurring? Are we part of the problem? If so, what can we do about it? In The End, award-winning writer Marq de Villiers examines these questions at a time when there is an urgent need to understand the perils that confront us, to act in such a way as best we can for the inevitable disasters when they come. We can do nothing about some natural calamities, but about others we can do a great deal. De Villiers helps us understand which is which, and lays out some provocative ideas for mitigating the damage all such calamities can inflict on us and our world. The End is a brilliant and challenging look at what lies ahead, and at what we can do to influence our future.